SOFT LAW SEBAGAI SEBUAH STRATEGI : STUD KASUS PIAGAM ASEAN (ASEAN CHARTER) - Fuat Albayumi (Universitas Wahid Hasyim Semarang, 2012)
Abstrak One indicator of the effectiveness of cooperation can be seen from: whether the agreement is soft law or hard law. Cooperation with soft law form tends to be ineffective because there is no binding consequences, while hard law form tend to be effective because the consequences are binding. Interestingly, countries drafting their cooperation in the form of soft law, at the expense of the effectiveness of their cooperation. By taking a case study of the ASEAN Charter, this article came to the conclusion that soft law chosen as a strategy to secure national interests when cooperation assessed no longer profitable. Key Word: Hard Law, Soft Law, Strategy